LANGUAGES OF FREEDOM IN DECOLONISING AFRICA*The Gladstone Prize Winner. (1st November 2017) - Hunter, Emma
ABSTRACT: The 'triumph of liberalism' in the mid-twentieth-century west is well known and much studied. But what has it meant for the way the decolonisation of Africa has been viewed, both at the time and since? In this paper, I suggest that it has quietly but effectively shaped our understanding of African political thinking in the 1950s to 1960s. Although the nationalist framing that once led historians to neglect those aspects of the political thinking of the period which did not move in the direction of a territorial nation-state has now been challenged, we still struggle with those aspects of political thinking that were, for instance, suspicious of a focus on the individual and profoundly opposed to egalitarian visions of a post-colonial future. I argue that to understand better the history of decolonisation in the African continent, both before and after independence, while also enabling comparative work with other times and places, we need to think more carefully and sensitively about how freedom and equality were understood and argued over in local contexts.